2016
DOI: 10.1177/0091217416659274
|View full text |Cite
|
Sign up to set email alerts
|

Improving patient-centered communication while using an electronic health record

Abstract: Data from our program evaluation demonstrated improvement in one communication behavior. Sample size limited the detection of other changes; further research should investigate effective training techniques for patient-centered communication while using the electronic health record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A good patient-physician relationship can strengthen diagnostic accuracy [6], increase both-side satisfaction [6,7], and decrease legal complaints [8]. Despite some initial concerns, structured communication has no contradiction with data entering into electronic health records [9] and physician's time management [10]. It might be imagined that only physicians should acquire communication skills.…”
Section: Management Of Difficult Patientsmentioning
confidence: 99%
“…A good patient-physician relationship can strengthen diagnostic accuracy [6], increase both-side satisfaction [6,7], and decrease legal complaints [8]. Despite some initial concerns, structured communication has no contradiction with data entering into electronic health records [9] and physician's time management [10]. It might be imagined that only physicians should acquire communication skills.…”
Section: Management Of Difficult Patientsmentioning
confidence: 99%
“…Despite these challenges, EHRs are now a part of the clinical care ecosystem and studies have identified actions that physicians can take to improve their interaction with both the patient and computer to provide more patientcentered care (11). For example, Fogarty et al identified a range of communication enhancing behaviors including the use of mobile monitors that can be shared with the patient, achieving a sufficient level of typing that does not require looking at the keyboard, explaining to the patient what you are entering into the EHR, pointing to specific elements on the screen to encourage patient engagement and reserving routine data entry for non-visit time (12). This last suggestion, while allowing more focus directly with the patient during the visit, is challenging, particularly in primary care where the burden of documentation is high (13).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Steps to take during patient visits Because entering information into the EHR can be distracting, be prepared to multitask during each clinical encounter. [1][2][3][4][5][6][7] Be ready to address pertinent inquiries and issues your patient raises, and provide instructions on therapies and interventions. Because interpersonal relations are important during clinical encounters, establish interaction with your patient by acknowledging them and maintaining frequent eye contact.…”
mentioning
confidence: 99%
“…7 In addition, lowering your overall stress might help reduce the burden of using the EHR. [3][4][5] Adopt healthy behaviors, including good sleep, nutrition, exercise, and hobbies, and strive for balance in your routines. Attend to any personal medical or psychiatric conditions, and avoid misusing alcohol, medications, or other substances.…”
mentioning
confidence: 99%